Clinical Features and Outcomes of Immunocompromised Adults Hospitalized with Laboratory-confirmed Influenza in the USA, 2011–2015. (4th October 2017) - Collins, Jennifer; Openo, Kyle; Farley, Monica; Cummings, Charisse Nitura; Ryan, Patricia; Yousey-Hines, Kimberly; Dufort, Elizabeth; Lynfield, Ruth; Lung, Krista; Thomas, Ann; Alden, Nisha; Kirley, Pam D; et al.
Abstract: Background: Data on immunocompromised (IC) adults with influenza are limited but suggest they may present differently and have worse outcomes than non-IC adults. Using a national surveillance system, we describe the epidemiology of IC adults hospitalized with influenza. Methods: We analyzed data on adults (aged ≥18 years) hospitalized with laboratory-confirmed influenza during the 2011–2012 through 2014–2015 seasons and reported to CDC's Influenza Hospitalization Surveillance Network (FluSurv-NET). We defined IC patients as having ≥1 of the following: HIV, AIDS, cancer, stem cell or organ transplantation, non-steroid immunosuppressive therapy, immunoglobulin deficiency, asplenia, and other rare conditions. We compared IC and non-IC patients using χ 2 or Fisher's exact tests and t -tests or Mann–Whitney U tests. Results: Among 35, 348 adults hospitalized over four seasons, 3, 633 (10%) were IC. The most common IC conditions were cancer (44%), non-steroid immunosuppressive therapy (44%), and HIV (17%). IC patients were younger than non-IC patients (mean 61 ± 17 vs. 67 ± 20 years; P < 0.01). IC patients were more likely to have underlying renal disease (27% vs. 18%) and liver disease (7% vs. 3%) and less likely to have most other chronic underlying conditions including obesity (18% vs. 23%), cardiovascular disease (40% vs. 47%), and chronic lung disease (35% vs. 41%; P < 0.01 for all). IC patients were more likely to have received influenza vaccination (53% vs. 46%; P < 0.01). Among cases with symptom data (2014–2015), IC patients were more likely to present with fever (68% vs. 61%; P < 0.01) but respiratory distress was similar (53% vs. 54%; P = 0.3). Overall, the majority of IC and non-IC patients received antivirals (87% vs. 85%; P < 0.01). IC patients had a longer duration of hospitalization (median (IQR) 4 (2–6) vs. 3 (2–6) days; P < 0.01) and were more likely to be diagnosed with pneumonia (34 vs. 31%; P < 0.01) and to require intensive care (18% vs. 16%; P = 0.01). Death during hospitalization occurred in 135 (3.7%) IC and 945 (3.0%) non-IC patients ( P = 0.01). Conclusion: Among adults hospitalized with influenza, IC patients had worse outcomes including a longer duration of hospitalization and higher probability of pneumonia and intensive care unit admission, and increased all-cause mortality, although these results are not adjusted for potential confounders. Disclosures: W. Schaffner, Pfizer: Scientific Advisor, Consulting fee. Merck: Scientific Advisor, Consulting fee. Novavax: Consultant, Consulting fee. Dynavax: Consultant, Consulting fee. Sanofi-pasteur: Consultant, Consulting fee. GSK: Consultant, Consulting fee. Seqirus: Consultant, Consulting fee. E. J. Anderson, AbbVie: Consultant, Consulting fee. NovaVax: Research Contractor, Research support. Regeneron: Research Contractor, Research grant. MedImmune: Research Contractor, Research grant and Research support